Exploring the alcohol use disorders risk level changes and influencing factors among Scottish residents from April (easing of restrictions) to June (after moving to level one restrictions) 2021 - Ma, Chunhui (The University of Edinburgh, 2021)
From December 2020, re-imposed lockdown can effectively control the spread of the COVID-19 epidemic in Scotland in winter. However, this sudden and prolonged life interruption will cause people to have psychological challenges. Drinking and even alcohol dependence can cope with the psychological pressure brought by this challenge quickly. Fewer studies exist on alcohol use changes after the COVID-19 pandemic in Scotland. Therefore, the objective of this study is to explore and investigate the risk level of alcohol dependence in Scottish adults before and after the lockdown lifting and its influencing factors. The 2302 online surveys used random sampling techniques in the lockdown (April 1st- April 10th) and after the release period (June 15th - June 25th) have performed correlation, spatial autocorrelation and geographical, and temporal weighted regression (GTWR) analysis on the relevant influencing factors studied. The results show that more than 60% of the respondents rated the alcohol dependence risk level as increasing risk and above levels. The proportion of people with possible alcohol dependence (22.5%) in home restriction is most significant than after the lockdown (8.5%), which is mainly affected by the infection status of the individual and relatives, as well as the high infection rate of the Datazone in which they are located influence. The AUDIT risk level of increasing risk and more of Scottish in Dundee and Aberdeen is affected by "accessible alcohol outlets density" and "health of relatives" Our research results have identified factors and local differences that affect the increase in AUDIT. The lockdown release policy effectively reduces the risk of alcohol dependence caused by trauma exposure. These factors can be used to formulate psychological interventions to improve the mental health of disadvantaged groups in local areas during the COVID-19 epidemic.
Keywords: COVID-19; Alcohol use disorder; Influencing factors; GTWR